Atmospheric Ice Accretion Measurement Techniques - Virk, Muhammad Shakeel; Mustafa, Mohamad Y; Hamdan, Qusai-Al (The International Journal of Multiphysics, 2011)
Atmospheric icing on structures has proven to be an area of concern in many cold climate geographical regions like arctic and alpine. Difficulties encountered by the communication, construction and power industries in these areas are the subject of intense investigations for researchers from decades. Three main methods of investigation are generally employed by researchers to study atmospheric ice accretion on structures: a) continuous field measurements, b) lab based simulations using icing wind tunnel & c) numerical modelling. This paper presents a brief review study of various techniques to understand and measure the atmospheric ice accretion on structures, anti/de icing techniques and important parameters for numerical modelling of atmospheric ice accretion.